Estimation of the rate of convergence to the limit distribution of the number of false solutions of a system of nonlinear random Boolean equations that has a linear part - Masol, V.; Slobodian, M. (Інститут математики НАН України, 2007)
The theorem on a estimation of the rate of convergence (n →∞) to the Poisson distribution of the number of false solutions of a beforehand consistent system of nonlinear random equations, that has a linear part, over the field GF(2) is proved.